#TITLE_ALTERNATIVE# - SURYA WIBOWO, DEDDY
The testing method that will be discussed in this paper is the “back pressure test method”. The author using the reservoir simulation method to estimate the opening time of natural flowing oil well . From this time, we can get the accurate parameter as the result of well test analization. The method is begun by entering the parameter to make a reservoir model. Then it is continued by doing the history matching and validate the result got by using the permeability sensitivity. Based on the reservoir modeling and through every step determined in the procedure, we get the opening time of the oil well. It is 82 hours with 100% accuracy. But, by the consideration about the cost of well test, we can take 22 hours with 70% accuracy. Then the validation is done using the permeability sensitivity with greater and lower values than the history matching at the reservoir simulation results.